The effect of nicotine and nicotine+monoamine oxidase inhibitor on the value of alcohol. Issue 4 (June 2019) - Frye, Charles C.J.; Galizio, Ann; Haynes, Jeremy M.; DeHart, William B.; Odum, Amy L.
Abstract : Alcohol is the most commonly abused drug in the USA and many people suffer from alcohol use disorder. Many factors are associated with alcohol use disorder, but the causal role of comorbid nicotine use has not been extensively considered. Nicotine has reward-enhancing properties and may increase the value of alcohol. Monoamine oxidase inhibition increases nicotine self-administration and may increase the reward-enhancing effects of nicotine. We assessed the effect of nicotine and nicotine in combination with a commonly used monoamine oxidase inhibitor (tranylcypromine) on the value of alcohol using a progressive ratio schedule of reinforcement in rats. Nicotine administration increased the breakpoint for alcohol, but nicotine in combination with tranylcypromine decreased the breakpoint for alcohol. The current study adds to previous research showing that nicotine increases the value of alcohol. This finding has important implications for the etiology of addiction because of the comorbidity of smoking with many drugs of abuse. The finding that nicotine in combination with tranylcypromine reduces the value of alcohol warrants further investigation.